The contribution of the polio eradication initiative to narrowing the gaps in the health workforce in the African Region. Issue 43 (10th October 2016) - Kamso, Jean; Mvika, Eddy S.; Ota, M.O.C.; Okeibunor, Joseph; Mkanda, Pascal; Mihigo, Richard
Highlights: A major challenge of health care delivery in Africa is gap in workforce. Investments for polio eradication tackled this problem. Polio eradication manpower helped to address the shortage of health workforce. Abstract: Introduction: The Global Polio Eradication Initiative (GPEI) massively invested to overcome the crippling disease in countries of the WHO African Region. In the context of economic crisis, almost all countries in the Region lack an adequate health workforce. Large amounts were invested by GPEI in human resources. This paper shows how the human resources funded by polio contributed to narrowing the gaps in health workforce and helped strengthening and supporting other priority health programmes in Angola, Chad, DRC, Nigeria, Tanzania, and Togo. Methods: The health workforce strengthening methods used in the five different countries included the following: policy development and strategic planning, microplanning, capacity building of public health and community workers, implementation and services, monitoring and evaluation, advocacy and social mobilization, and programme review. Results: Staff funded by polio helped with achieving good coverage in vitamin A and insecticide-treated mosquito nets (Angola, Chad); improvement of EPI and integrated disease surveillance indicators, improved quality of data (all five countries), administrative support, smooth introduction of new vaccines, increased case detection, and early isolation of patients suffering from the Guinea worm (Chad); reduction of cholera, extension of directly observed TB short course treatment (Democratic Republic of Congo); significant staff performance improvement (Nigeria). Discussion: GPEI investment achieved far beyond its primary goal, and contributed to narrowing the gaps in the health workforce in countries of the African Region, as demonstrated by the best practice documentation exercise. We recommend that expertise and experience of polio funded staff should be leveraged to strengthen, expand and support other public health programmes.